The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1021/ja994044n
|View full text |Cite
|
Sign up to set email alerts
|

Diprotonated Hydrogen Halides (H3X2+) and Gitonic Protio Methyl- and Dimethylhalonium Dications (CH3XH22+ and (CH3)2XH2+):  Theoretical and Hydrogen−Deuterium Exchange Studies1

Abstract: Density functional theory (DFT) calculations at the B3LYP/6-31G** level were performed to investigate geometries and energies of a series of diprotonated hydrogen halides (H 3 X 2+ ) and gitonic protio methyl-and dimethylhalonium dications (CH 3 XH 2 2+ and (CH 3 ) 2 XH 2+ ). On the basis of computed energies, proton affinities and related thermodynamic parameters were also calculated. A hydrogen/deuterium exchange experiment of dimethylbromonium ion, (CH 3 ) 2 Br + , with an excess of 4:1 DF/SbF 5 superacid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…The earlier calculations by B3LYP/6-31G(d,p) and B3LYP/6-31+G(d,p) methods of di-and trialkylhalogen cations [2,3] have shown that they possess an angular structure, and the positive charge on the halogen atom grows in a series F, Cl, Br, I in the full agreement with the decrease in their electronegativity.…”
mentioning
confidence: 72%
“…The earlier calculations by B3LYP/6-31G(d,p) and B3LYP/6-31+G(d,p) methods of di-and trialkylhalogen cations [2,3] have shown that they possess an angular structure, and the positive charge on the halogen atom grows in a series F, Cl, Br, I in the full agreement with the decrease in their electronegativity.…”
mentioning
confidence: 72%
“…Most of the halonium ions except for fluor has been prepared as stable dialkyl chloro-, bromo-, and iodohalonium ions as long-lived ions. Theoretically, it has been calculated for (CH 3 ) 2 X + that the C-C distances are 2.66Å (X = F), 2.94Å (X = Cl), 3.10Å (X = Br), and 3.33 Å (X = I) and the corresponding CXC angels are 120.2˚ (X = F), 105.0˚ (X = Cl), 101.4˚ (X = Br), and 97.7˚ (X = I) [20] [21]. In excellent correspondence with these results is the recent chemical and theoretical evidence for a symmetrical fluoronium ion in solution [22].…”
Section: Hydrogen and Fluor Transitions As Divalent Atoms In A Three-mentioning
confidence: 99%
“…This reaction involves hydridohalonium ions 126 as intermediates that subsequently undergo nucleophilic attack by excess alkyl halide. Protonation of methylhalonium ions to form diprotonated dications CH 3 XH 2 2þ have been calculated (B3LYP/6-31-G** level) 348 to occur primarily on the CÀH bond to form a pentacoordinated carbon with 2e-3c bond. 349 These hydridohalonium ions have been characterized by 13 C NMR spectroscopy.…”
Section: Acyclic (Open-chain) Halonium Ionsmentioning
confidence: 99%
“…Olah, Rasul, Prakash, and co-workers 348 have calculated the structure and stability of protonated dimethylhalonium dications (CH 3 ) 2 XH 2þ (B3LYP/6-31-G** level). Dialkyl alkylenedichloronium ions have not yet been directly observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation